Bimbingan dan Konseling Islam untuk Pasien Rawat Inap di Rumah Sakit - Arifin, Isep Zainal (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2012)
One of the interesting and important problem that faced by patients at hospital is the ignoring of their spiritual need. However if this aspect cannot be fullfilled then patients will get psychological and theologicat effects and it is against patients right and nursing ethics. More of the patients at hospital are moslem, then the solution is there must be a research to find an islamic guidance and counseling programe which is able to serve the moslem spiritual needs because this spiritual needsÂ cannot be fulfilled by general nursing sevices.